Moderating role of mindfulness and social support in the relationship between fertility pressure and fertility quality of life in Chinese infertile men - Lihuan Zhi; Jumanali Mireyi; Abulizi Maierhaba; Hua Xu; Lijuan He; Jiangabieke Lizha (PLoS ONE, 2025)
Men with infertility are susceptible to fertility pressure, thus affecting their fertility quality of life. To develop fertility-pressure resilience interventions, we investigated whether mindfulness and social support could buffer the association between perceived fertility pressure and fertility quality of life in Chinese infertile men. In this cross-sectional study, Chinese men with infertility who visited the clinic for semen examination completed the Fertility Pressure Inventory, Mindful Attention Awareness Scale, Social Support Scale, and Fertility Quality of Life Scale online. In total, 469 Chinese infertile men (mean age: 32 years) were recruited, of whom 414 (88.3%) reported no childbearing history or high fertility stress. Analysis using generalised linear models revealed that social support had a moderating effect on the association between reproductive stress and reproductive quality of life (F = 11.006, P = 0.001), and between the core (F = 9.063, P = 0.003) and treatment (F = 9.383, P = 0.002) subdimensions of reproductive quality of life and reproductive stress. Among men with high social support scores, the association between reproductive stress and reproductive quality of life (t = −3.146, P = 0.002) and the core subdimension (t = −3.333, P = 0.001) was significant, whereas among men with low social support scores, the association between reproductive stress and reproductive quality of life (t = 0.906, P = 0.365) and the core subdimension (t = 0.266, P = 0.790) was not significant. Mindfulness did not significantly regulate fertility stress and reproductive quality of life(F = 1.528, P = 0.217), its core (F = 1.406, P = 0.236) and treatment (F = 1.026, P = 0.312) subdimensions. Higher social support levels attenuated the negative association between fertility stress and reproductive quality of life (including core dimensions) in infertile men. Experimental studies are needed to determine whether social support is a protective factor.